144k views
2 votes
If f(x)= x^1/2 - x and g(x)= 2x^3 - x^1/2 - x, find f(x) - g(x)

If f(x)= x^1/2 - x and g(x)= 2x^3 - x^1/2 - x, find f(x) - g(x)-example-1

1 Answer

6 votes

Answer:


-2x^3+2x^(1/2)

Explanation:

First, you have to substitute both functions into the equation to get:


f(x)-g(x) = (x^(1/2)-x) - (2x^3-x^(1/2)-x)

Then, you distribute the negative sign in front of g(x) to get:


= x^(1/2) - x -2x^3+x^(1/2)+x

And finally, you add/subtract the x's that have the same power to get:


=-2x^3+2x^(1/2)

User Florisla
by
4.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.